1999
DOI: 10.1523/jneurosci.19-22-j0001.1999
|View full text |Cite
|
Sign up to set email alerts
|

t  Asymmetric Connections, Duplicate Layers, and a Vertically Inverted Map in the Primary Visual System

Abstract: The achiasmatic mutation is a remarkable and rare visual system mutation carried in a line of black sheepdogs. In affected animals, the optic chiasm is missing, and each retina projects entirely to the ipsilateral hemisphere. As a result of this navigational error, maps of visual space in the lateral geniculate nucleus (LGN) have a unique structure with mirror reversals of field position across the A-A1 border. Animals also have a persistent and severe congenital nystagmus. In this report we analyze a novel va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…A study of 2 patients has suggested that achiasmatic patients have deranged retinotopic maps in the occipital cortex despite relatively normal visual fields and perception (15). This type of altered anatomy and physiology has also been reported in the lateral geniculate nucleus and visual cortex of achiasmatic Belgian sheepdogs, with dramatic discontinuity of receptive field representations and proximity of neurons that respond to visual stimuli on opposite sides of the visual field (9,10,16)…”
Section: Discussionsupporting
confidence: 54%
“…A study of 2 patients has suggested that achiasmatic patients have deranged retinotopic maps in the occipital cortex despite relatively normal visual fields and perception (15). This type of altered anatomy and physiology has also been reported in the lateral geniculate nucleus and visual cortex of achiasmatic Belgian sheepdogs, with dramatic discontinuity of receptive field representations and proximity of neurons that respond to visual stimuli on opposite sides of the visual field (9,10,16)…”
Section: Discussionsupporting
confidence: 54%
“…The effects of the loss of endogenous activity may be buffered at higher levels of the visual pathway (Weliky and Katz 1999). An example of such buffering is found in the hemichiasmatic dog (Hogan et al . 1999a).…”
Section: Discussionmentioning
confidence: 99%
“…In one type, most of the retinal ganglion cells of both eyes project to the lateral geniculate nucleus of one hemisphere and not the other. (57) In the other phenotype, retinal axons of each eye project only to the ipsilateral hemisphere. (58) Nevertheless, topological maps of the altered inputs were found in visual cortex.…”
Section: Disruptions In the Sensory Sheet Are Reflected By Septa In Smentioning
confidence: 99%